ChemInform Abstract: Crystal Structures of MBi2Br7 (M: Rb, Cs) — Filled Variants of AX7 Sphere Packing. Issue 25 (June 2016) - Chang, Jen‐Hui; Wolff, Alexander; Ruck, Michael
Abstract: The title compounds are new phases in the systems MBr—BiBr3 (M: Rb, Cs).